Smartphone Use and Sleep Quality in Chinese College Students: A Preliminary Study - Huang, Qiuping; Li, Ying; Huang, Shucai; Qi, Jing; Shao, Tianli; Chen, Xinxin; Liao, Zhenjiang; Lin, Shuhong; Zhang, Xiaojie; Cai, Yi; Chen, Hongxian (Frontiers in Psychiatry, 2020)
Background: Chinese college students are at high risk for sleep problem and smartphone use is common among this population. However, the relationship between smartphone use characteristics and sleep problem is inadequately studied in Chinese college students. In this preliminary study, we examined the association of poor sleep quality with smartphone use in a sample of Chinese college students from a health vocational college in Changsha, China. Methods: A total of 439 college students completed a self-report questionnaire, containing the Pittsburgh Sleep Quality Index (PSQI) and questions regarding demographic information, psychosocial factors, physical health, smartphone use characteristics, and mobile phone addiction (MPA). Results: The results showed that the prevalence of poor sleep quality (PSQI > 7) in Chinese college students was 9.8%. In multiple logistic regression analysis, poor sleep quality was significantly associated with male gender (OR: 2.80, P: 0.022), not having good physical health (OR: 2.61, P: 0.020), headache (OR: 2.47, P: 0.014), more depressive symptoms (OR: 2.17, P: 0.049), > four years of smartphone use (OR: 3.38, P: 0.001), > five hours of daily smartphone use (OR: 2.19, P: 0.049), and more severe inability to control craving of MPA (OR: 2.04, P: 0.040). Conclusion: Our findings suggest that excessive smartphone use and MPA are associated with poor sleep quality in a sample of Chinese college students from a health vocational college. Because of the limited sample representativeness and cross-sectional design of this study, large-scale prospective representative studies are warranted to confirm these associations.